Dashboard para visualizar la calificación del proceso de peticiones de PQRD de las entidades de salud en Colombia (2021)
An analysis of the status of the attention of petitions, complaints, claims and complaints (PQRD) filed before the Superhealth by users affiliated with the health system in Colombia, which allowed knowing the variables to deduce the need to develop a dashboard to display the rating of health entities in accordance with PQRD status. Therefore, it is proposed to implement the RIM method for the transformation of the PQRD data obtained from the open data platforms of Colombia and Supersalud for the years 2018 and 2020, then the data prepared is loaded into a database. data for availability before the Tableau tool, in which a dashboard is built for the visualization of the qualification of health entities for end users.